2013
DOI: 10.2298/vsp1307675s
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species, apoptosis and cancer

Abstract: Projekat Ministarstva nauke Republike Srbije, br. 17509

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 41 publications
0
11
0
1
Order By: Relevance
“…(3) Mitochondrial dysfunction, which may promote cell death. It has been shown that ROS can initiate the apoptotic cascade via increasing the permeability of the mitochondrial membrane [21]. (4) Phagosome maturation, which involves the fusion between phagosomes and intracellular organelles and has been implicated in the elimination of cells that have undergone apoptosis [31].…”
Section: Discussionmentioning
confidence: 99%
“…(3) Mitochondrial dysfunction, which may promote cell death. It has been shown that ROS can initiate the apoptotic cascade via increasing the permeability of the mitochondrial membrane [21]. (4) Phagosome maturation, which involves the fusion between phagosomes and intracellular organelles and has been implicated in the elimination of cells that have undergone apoptosis [31].…”
Section: Discussionmentioning
confidence: 99%
“…Increased fluxes of free radicals are associated with biomolecule damage and play a key role in the initiation of various complications such as cardiovascular diseases 15 and cancer. 16 The final products of lipid peroxidation have an important role in activating oncogenes by interfering with the balance between the antioxidant/oxidative stress system and through expression of some genes that contribute to cancer initiation and progression. 17 We found that the antioxidant activities of PON1 and ARE were significantly lower in MM patients compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Reactive species have been implicated in different stages of carcinogenesis, including initiation, promotion and progression . Reactive species are important inducers of cancer by inducing DNA mutations, activating oncogenes and inhibiting tumor suppressor genes . In several animal experiments, an increase in antioxidant capacity has been suggested to lead to better cancer outcomes .…”
Section: The Dual Roles Of Reactive Species In Diseasementioning
confidence: 99%